(untitled) - Rydberg, Terry (Clifton Park, NY, 2006)
In the real world, page layout projects don't come with directions and the "recipe book" approach of most software books does little to prepare designers for the demands of a highly competitive industry. Exploring InDesign CS2 takes a different approach. With an emphasis on typography and critical thinking, the book transforms the novice into a professional typesetter- one who is grounded in industry-standard design principles. In addition to gaining professional proficiency while using the new features of Adobe InDesign CS2, users learn to begin a project while visualizing the end design, to identify the project pitfalls and challenges, and to independently strategize the best production sequence. Chapters and projects are carefully ordered to move readers from basic operations to creating complex documents using multiple master pages and paragraph and character styles, with each chapter building upon the skills presented in the previous chapter. As in industry, the emphasis throughout is on productivity, including preplanning and utilizing keyboard shortcuts.
Keywords: Adobe InDesign,Desktop publishing,Kỹ thuật in ấn,Thiết kế hình nền